Silica-supported chromium oxide: colloids as building blocks - Hermans, Ive; Breynaert, Eric; Poelman, Hilde; De Gryse, Roger; Liang, Duoduo; Van Tendeloo, Gustaaf; Maes, André; Peeters, Jozef; Jacobs, Pierre (Physical chemistry chemical physics : PCCP, 2007)
In this contribution, the formation and immobilisation of chromium(iii) hydroxyoxide colloids is investigated. Nano-sized Cr(iii) colloids are generated in situ upon reduction of Cr(vi), dosed to a stirred reactor. The growth of the elementary colloids by the consumption of solved Cr is kinetically unfavorable compared to their aggregation to larger secondary particles, the size of which depends on the concentration of the building block colloids. This aggregation process can be steered by simple process parameters such as dosing rate and concentration of the Cr(vi). The Cr(iii) colloids are immobilised in situ on a support material via precipitation chromatography. Upon drying, the initially amorphose hydroxyoxides are gradually transformed into crystalline Cr(2)O(3) nanoparticles, mainly located at the external surface of the support. This approach opens new opportunities for the synthesis of supported metal oxide catalysts.